Outcomes of Patients With Late-Relapse Metastatic Renal Cell Carcinoma Treated With Targeted Therapies: A Single Institution Experience - Kucharczyk, John (Ochsner J, 2017)
BACKGROUND: Late relapse with presentation of metastatic disease >5 years after nephrectomy with curative intent is a known behavior of renal cell carcinoma (RCC), but data on outcomes, especially regarding targeted therapies, are limited. In this study, we analyze clinicopathologic features and response to targeted therapy in patients with late-relapse metastatic RCC (mRCC). METHODS: We retrospectively reviewed clinical data on consecutive patients treated with targeted therapy for mRCC diagnosed >5 years after nephrectomy with curative intent. RESULTS: A total of 24 patients (100% clear cell histology, median age 72 years, 83% males, all with prior nephrectomies) met inclusion criteria; 71% had favorable risk, and 25% had intermediate risk by International Metastatic Renal Cell Carcinoma Database Consortium criteria. The estimated median overall survival for all patients was 60.5 months, and the 3-year overall survival rate was 71.78% (95% confidence interval, 47.98%-84.77%). All patients were treated with targeted therapy; first-line treatments included pazopanib (46%), sorafenib (25%), sunitinib (17%), and cytokine (13%), with no significant difference in time to treatment failure between therapies. Median time on first-line therapy was 19.7 months; 67% of patients received second-line treatment. Metastases were detected at considerable rates in sites considered historically uncommon, such as the pancreas, adrenal glands, and soft tissue. CONCLUSION: Patients with late-relapse mRCC treated with targeted therapy had prolonged survival that compared favorably to historical controls, and metastases in uncommon sites were noted.